Ciência e ética em Karl Popper - DIAS, Leandro José dos Passos (Universidade Federal do Pará, 2022)
The more traditional studies about Popper’s philosophy have focused on aspects of his theory of science or his political philosophy or, even, on establishing links between them. More recently, new studies have emerged pinpointing a new hermeneutics that aims to show that ethics is at the root of his philosophy. Our work, assuming that there is an ethics at the base of his thought, intends to analyze it from a more specific perspective: that of science itself. Thereby, we will investigate the following question: can we say that Popper's conception of science involves an ethical dimension? Or rather, is there a relationship between science and ethics in the philosopher’s thought? We will consider that his notion of science presupposes an ethics, which is manifested in his pretensions to demarcate science, in the principles that guide it and in the responsibilities he assigns to scientists. Our analysis of the issue intends to start from Popper’s own rationalism, which he considers as the result of an ethical decision. In this sense, we seek to analyze its character, distinguish it from other forms of rationalism, oppose it to irrationalism and uncover its ethical foundations assisted by the studies of Kiesewetter, Artigas and Oliveira. In addition, to stablish its relations with ethics. Once these characteristic aspects of Popper’s rationalism have been clarified, we will try to show how ethics is present in his conception of science. We’ll show that Popper, when proposing his criterion of scientificity and complementing it with certain methodological rules, makes it clear that the adoption of such rules involves scientists’ decisions based on values and also generates certain ethical commitments. Furthermore, we intend to demonstrate that ethics is present in the ethical principles that guide science, such as fallibility, reasonable discussion, search for truth, honesty and that such principles are closely related to the idea of selfcriticism and tolerance. Finally, we will address the ethical responsibilities of scientists, emphasizing applied sciences. We will show that Popper proposes a new ethics for Science based on the Hippocratic oath.